The Effect of a Mixture Bioetanol and 92 Octane Fuel on Motorcycle Exhaust Gas Emissions - dani, Agus; Winoko , Yuniarto Agus; Santoso, Santoso; Listiyono, Listiyono (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
High concentrations of pollutants from incomplete combustion of motor vehicles have an impact on the surrounding environment and the health of living things. Incomplete combustion as a result of the design of the combustion chamber and the type of fuel used that does not correspond to its compression ratio. To improve the octane value of the fuel can be mixed bioethanol, because this alternative fuel is environmentally friendly. The purpose of knowing how much the change in the emission values of CO, HC, O2 and CO2 when using 92 octane fuel, and 95. additionally determines the change when using 92 octane fuel mixed with bioethanol 5, 15, 25%. The method of mixing fuel with bioethanol using splash blending method and exhaust emission testing based on dynamic method when the engine speed of 1250 to 9000rpm to obtain data. Furthermore, the test data processed by ANOVA. The result is a change in emissions of 0.07% CO, 16ppm HC, 2.3% CO2 and 0.2% oxygen at Octane 92, the change in emissions was 0.32 CO, 54ppm HC, 1.54% CO2 and 0.44% O2 when using BE25% fuel mixed with 95octane